Problems in the Status of Object Ownership of Ijarah Muntahiyah Bittamlik Financing Contract in Sharia Banking Law (Journal of Private and Commercial Law, 2019)
The crisis of faith and economic crisis accompanied by an increase in economic needs encourages one to find the right way, as well as the efforts made by producers and industry in marketing products without seeing the halal and haram provisions of a product. These reasons cause a variety of mu'amalah through financing agreements began to emerge, such as lease agreements known to the public with the term leasing introduced by Islamic financial institutions under the name Ijarah Muntahiyah Bittamlik, so this study aims determine the ownership status of the object of the Ijarah Muntahiyah Bittamlik financing contract. The author believes that the ownership status of the contract object on the financing of Ijarah Muntahiyah Bittamlik raises legal issues because of the unification of the contract between the lease and the sale and purchase which depends on the repayment of all the value of the goods.